1994
DOI: 10.1002/bit.260440412
|View full text |Cite
|
Sign up to set email alerts
|

Transport of bacteria in porous media: I. An experimental investigation

Abstract: The convective transport of concentrated suspension of bacteria in porous media is of interest for several processes such as microbial enhanced oil recovery and in situ bioremediation. The parameters which affect the transport of the bacterium Bacillus licheniformis JF-2, a candidate microorganism for microbial enhanced oil recovery, were investigated experimentally in sandpacks. Bacteria retention and permeability reduction occurred primarily in the first few centimeters upon entering the porous medium. In do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…It can be observed from the figure that an increase in the space time from 13.13 to 34.34 min significantly decreased the number of E. coli in the CAACO-treated wastewater. Lower purification, as a result of higher flow rate, has been observed in several experiments (Smith et al, 1985;Gannon et al, 1991;Sharkar et al, 1994;Lawarence and Henry, 1996). It is known that high flow rate (Q) or low space time (t) increase the water velocity through voids in the carbon bed and reduces the exchange between carbon particles and mobile water.…”
Section: Effect Of O 2 /Codmentioning
confidence: 83%
“…It can be observed from the figure that an increase in the space time from 13.13 to 34.34 min significantly decreased the number of E. coli in the CAACO-treated wastewater. Lower purification, as a result of higher flow rate, has been observed in several experiments (Smith et al, 1985;Gannon et al, 1991;Sharkar et al, 1994;Lawarence and Henry, 1996). It is known that high flow rate (Q) or low space time (t) increase the water velocity through voids in the carbon bed and reduces the exchange between carbon particles and mobile water.…”
Section: Effect Of O 2 /Codmentioning
confidence: 83%
“…The base fluid is a dilute water solution of nutrients in which the microorganisms can live and flow though the porous medium. From experimental results, it has been observed that the microorganisms can withstand temperatures of 42 °C (Sarkar et al [21]). The effect of the magnetic field appears when the magnetite (Fe3O4) nanoparticles (of size 10-250 nm) are suspended in the base fluid with concentration less than 1%.…”
Section: Mathematical Formulationmentioning
confidence: 96%
“…Convective transport of concentrated suspensions of bacteria in porous media has interesting applications in areas of microbial enhanced oil recovery and in situ bioremediation. Sarkar et al [21] experimentally investigated the convective transport of bacteria in porous media subject to effects such as the addition of a dispersant and wall suction/injection. Subsequently, a model for the convective transport and growth of bacteria in porous media was depicted by Sarkar et al [22].…”
Section: Introductionmentioning
confidence: 99%
“…The bulk cell concentration also has a significant effect on the rate at which a porous matrix may be plugged by deposition (Jang et al, 1983;Sarkar et al, 1994). Although flow-induced deposition can lead to a decrease in permeability, it has also been shown that, without the production of exopolymers in a highly permeable matrix, there is no change in system permeability (Lappan and Fogler, 1992).…”
Section: Introductionmentioning
confidence: 96%